Capillary Malformation–Arteriovenous Malformation Combined Alagille Syndrome in a Patient With Double Gene Variations of RASA1 and NOTCH2 - Zheng, Yu; Peng, Yuming; Zhang, Shuju; Li, Liping; Peng, Yu; Yin, Qiang (Frontiers in Genetics, 2019)
Background: Capillary malformation–arteriovenous malformation (CM-AVM) is an autosomal dominant disorder characterized by CMs, often in association with fast-flow vascular malformations. Alagille syndrome is an autosomal dominant multisystem disorder, usually involving hepatic, cardiac, ophthalmic, skeletal, or renal dysplasia. The combination of CM-AVM and Alagille syndrome in a patient presenting serious vascular malformations in the liver and heart has never been reported. Here, we report the case of a 20-month-old infant presenting these two diseases. Case presentation: The patient manifested port-wine stains, congenital heart disease, cholestasis with abnormal morphology, and vascular anomalies. Color Doppler (B-mode) ultrasonography, and radiological imaging including computed tomography (CT) with enhanced three-dimensional (3D) reconstruction and angiography, revealed a type II Abernethy malformation in the hepatic portal vein. The left hepatic lobe was enlarged showing dilation of the portal vein and the left artery. Whole exome sequencing (WES) identified a paternally inherited RASA1 heterozygous pathogenic variant p.(Ser219Ter) causing CM-AVM and a de novo NOTCH2 heterozygous variant p.(Met2042Thr) associated with Alagille syndrome. Conclusion: This is the first case of combined CM-AVM and Alagille syndrome presenting serious liver and heart abnormalities diagnosed using imaging technology and WES. The patient harbored variants in two genes: RASA1 and NOTCH2, which rarely contribute to aberrant vascular development. This report highlights the value of accurately diagnosing similar diseases and guiding therapy using genetic testing combined with careful clinical examinations.